2017
DOI: 10.1016/j.idcr.2017.06.013
|View full text |Cite
|
Sign up to set email alerts
|

A case of liver abscess and fusobacterium septicemia

Abstract: Fusobacterium species are well described as the causative pathogen in Lemierre’s syndrome, a suppurative thrombophlebitis of the jugular vein. However, they are less recognized for a unique variant of Lemierre’s syndrome presenting with invasive intraabdominal infection and associated portal vein thrombosis. We describe a case of Fusobacterium nucleatum with hepatic abscess and septic pylephlebitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…[13] Rahmati et al reported a case of an hepatic abscess secondary to Fusobacterium infection, causing pylephlebitis. [14] In our case, we believe the liver abscesses preceded the development of the pylephlebitis of the left portal vein due to negative blood cultures. Previous cases have been reported on potential local seeding of infection such as in a case presented by Tandon et al identified pylephlebitis complicating a liver biopsy.…”
Section: Discussionmentioning
confidence: 58%
“…[13] Rahmati et al reported a case of an hepatic abscess secondary to Fusobacterium infection, causing pylephlebitis. [14] In our case, we believe the liver abscesses preceded the development of the pylephlebitis of the left portal vein due to negative blood cultures. Previous cases have been reported on potential local seeding of infection such as in a case presented by Tandon et al identified pylephlebitis complicating a liver biopsy.…”
Section: Discussionmentioning
confidence: 58%
“…We hereby report a case of septic portomesenteric thrombosis secondary to Fusobacterium necrophorum bacteremia in the setting of sigmoid colitis to add to a total of 21 cases of Fusobacterium - spp. -infection-related pylephlebitis reported in the literature [ 8 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, there have only been four other cases of Fusobacterium hepatic abscess associated with pylephlebitis in the international literature [4,5,7,8]. In some of the previous cases, the patients were treated with both anticoagulation and antibiotics.…”
Section: Discussionmentioning
confidence: 99%